Difuzija ničel polinomov - Vrbica, Mile (Matrika, 2019)
This article studies the behaviour of polynomial roots where its time evolution is governed by the diffusion equation. The dynamic equation for roots will be derived. Collisions of roots will be explained, as will be their dynamics in the complex domain. Theoretical predictions will be compared to numerical results.
Keywords: collisions of roots; diffusion equation; difuzijska enačba; dinamika ničel; dynamics of roots; ničle polinoma; polynomial roots; trki ničel